2011
DOI: 10.1007/s00540-011-1203-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flurbiprofen, metoclopramide and droperidol for nausea and emesis during cesarean section under spinal anesthesia

Abstract: Intravenous flurbiprofen improves nausea and emesis after delivery by cesarean section more effectively than metoclopramide or droperidol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Current studies have suggested that non-steroidal drugs positively affect UCP [14]. For example, flurbiprofen axetil is a non-selective non-steroidal drug, and it is safe for females who are breastfeeding in the early postpartum period [15,16]; thus, it is also safe for cesarean section analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have suggested that non-steroidal drugs positively affect UCP [14]. For example, flurbiprofen axetil is a non-selective non-steroidal drug, and it is safe for females who are breastfeeding in the early postpartum period [15,16]; thus, it is also safe for cesarean section analgesia.…”
Section: Introductionmentioning
confidence: 99%